PENGARUH ETIKA DAN PELAYANAN PRIMA CUSTOMER SERVICE TERHADAP TINGKAT KEPUASAN NASABAH PADA PT BANK SUMSEL BABEL CABANG PRABUMULIH - Yudi Tusri; Chairani Adelina; Sri Suparni (Jurnal Manajemen Bisnis Unbara, 2022)
This study aims to determine the effect of ethics (X1) and excellent service (X2) customer service partially and simultaneously on the level of customer satisfaction (Y) at PT Bank Sumsel Babel Prabumulih Branch.This study uses quantitative research methods with a descriptive approach. The type of data used is primary data, which means data obtained directly from respondents. In this study, the questionnaires were distributed to 89 respondents. The test used to test the research instrument is the validity test, reliability test, classical assumption test, hypothesis test and determination test (R2). Ethics (X1) partially affects customer satisfaction at PT Bank Sumsel Babel Prabumulih Branch. The ethical regression coefficient (X1) is 0.458. This can be seen from the results of the study which showed that tcount > t table or 3,738 > 0.67726, with a significant value of 0.000 < 0.05. Excellent service (X2) partially affects customer satisfaction at PT Bank Sumsel Babel Prabumulih Branch. Based on the results of the research, the regression coefficient for excellent service (X2) is 0.417. This can be seen from the results of the study which showed that tcount > t table or 3.514 > 0.67726, with a significant value of 0.001 < 0.05. Ethics (X1) and excellent service (X2) simultaneously affect customer satisfaction at PT Bank Sumsel Babel Prabumulih Branch by 60.5%. This can be seen from the results of the study which showed that Fcount > Ftable or 68.316 > 3.952, with a significant value of 0.000 < 0.05. This research was conducted with a qualitative descriptive method. To obtain more significant results, it is better to add other variables that can affect customer satisfaction at Bank Sumsel Babel, such as promotions, location, facilities that may affect the level of customer satisfaction. This research contributes to the development of literature, especially public sector accounting and can be a suggestion to local governments in improving the level of publication of their financial statements on the website so that transparency and accountability in regional financial management increases and clean governance can be realized.